Energy and Exergy Analysis of ALkhoms Gas Turbine Power Plant Under Part Load Operating Conditions - Waleed Omymen; Ali Ebshish; Ahmed Beshish; Abdelrahman Saleh Sultan (African Journal of Advanced Pure and Applied Sciences, 2026)
The gradual increase in electricity demand has resulted in the expansion of power stations. Such an expansion centered on building new power plants and revamping the existing ones to improve efficiency. The objective of this study is to perform an exergy analysis on the Khoms Gas Turbine Power Plant (KGTPP), which utilizes two different types of fuel: light diesel and natural gas at different loads. Here, mass and energy conservation were applied to the power station components (gas turbine, combustion chamber, and compressor) with different loads and pressure ratios. The results showed that when natural gas was used, the largest exergy destruction of up to 290.86 MW occurred in the combustion chamber. Meanwhile, the lowest exergy destruction of 9.1 MW occurred in the compressor. According to the first law, the thermal efficiency of the gas turbine power plant was 34.3%, while exergy efficiency was 32.5%. For the light fuel power station, results showed that the largest exergy destruction of up to 219.33 MW occurred in the combustion chamber. Meanwhile, the lowest exergy occurred in the compressor at 5.68 MW. According to the first law, the thermal efficiency of the gas turbine power plant was 36.8% and exergy efficiency was 35%. The results demonstrated a significant correlation between changes in the power plant load and the overall energy and exergy efficiencies, as well as exergy destruction.